(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: Normal tension glaucoma (NTG) is the form of the disease in which damage to the optic nerve occurs at normal intraocular pressure levels. According to Levene, four times as many patients in the over 40 age group have NTG as have high tension glaucoma, accounting for 2% of the Japanese population. Purpose: To present a clinical case exemplifying the diagnosis and treatment of NTG. Materials and Methods: The patient underwent assessment of the level of visual acuity, ophthalmoscopy, intraocular pressure and visual field examination, and optical coherent tomography (OCT). Results: The patient was diagnosed with NTG. The clinical diagnosis was confirmed by examinations performed (i.e., ophthalmic rheography, OCT, visual field perimetry and ocular tonography).